Projecto de reconversão: "Arquitectura Contemporânea Face ao Espaço Rural" - Paulo Miguel Teixeira de Morais (2014)
This dissertation presents a concrete project for the conversion of a rural property into a residence for leisure time, for a family consisting of three cores from three different generations. The intervening space is a property with an agricultural vocation (fruit and vegetable), with about an acre, situated in Mourisca do Vouga, in a marginal interface area between urban and rural, and that has been belonging to this family for some generations. It includes, besides fruit trees and vegetables, a forest area, the residence house and other outbuildings to support agricultural activity. The project was elaborated in accordance to a detailed plan, previously conceived in order to consider the required functionality, comprising new structures (residential and recreational) in addition to the existing ones, which favour a contemporary aesthetic. The renovation of existing houses (a referential identity of the family) preserved the internal reading spaces, but renewed the external reading considering a global aesthetic choice. The unity / identity of the architectural overall, where current volumes (in particular the most emblematic) are highlighted, is preserved by the use of mimetic solutions for the integration of new spaces and by the formation of the openings rhythm; the interior and exterior space of socialization are diverse, respecting the option for individual reclusion by an unambiguous demarcation of intimate spaces. The enjoyment of the internal and external landscaped environment is preserved, in areas where the housing structure faces the rural; however, in the encounter of the housing core with the adjacent urban space, privacy is enhanced, without prejudice (or better, with benefit) to the harmony with the adjacent space. This concern about the impact on the environment of the intervention proposed is also showed by the maintenance of the height and nature of the material of the wall boundaries ABSTRACT of the property and of the profile of outstanding volumes. In this dissertation, the implicit confrontation between an architectural project and the theory is underlying in the search for indicators for the "space design conception", integrated into the relation of contemporary architecture with the rural element (in a 'temporary alternative housing' perspective). The most relevant theoretical standpoints, which are at the foreground of the referred demand and at the genesis of this project, are based on an objective review of the "state of the art ", and include the theoretical framework that aims to encompass concepts of dwelling, with particular emphasis on its inherent social part - that is, the interactions of a cohabiting household and the relationship between creator / user through which the "symbiosis" of these terms is enabled. In this context, a particular focus is given to significant texts and reflections of the twentieth century onward with emphasis to the "modern"